2014
DOI: 10.1016/j.ajo.2013.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Dry Eye in the Beaver Dam Offspring Study: Prevalence, Risk Factors, and Health-Related Quality of Life

Abstract: Purpose To estimate dry eye prevalence in the Beaver Dam Offspring Study (BOSS), including a young adult population, and investigate associated risk factors and impact on health-related quality of life. Design Cohort study. Methods The BOSS (2005–2008) is a study of aging in the adult offspring of the population-based Epidemiology of Hearing Loss Study cohort. Questionnaire data on health history, medication use, risk factors, and quality of life were available for 3275 participants. Dry eye was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
229
5
21

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(272 citation statements)
references
References 28 publications
17
229
5
21
Order By: Relevance
“…[1][2][3]6,7,[9][10][11][14][15][16][17][18][19][20][21][22][23] There is scarce information about the natural history of dry eye, but there is a recognized disconnection between signs and symptoms; patients tend to be more symptomatic at early stages.…”
Section: Dry Eye Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]6,7,[9][10][11][14][15][16][17][18][19][20][21][22][23] There is scarce information about the natural history of dry eye, but there is a recognized disconnection between signs and symptoms; patients tend to be more symptomatic at early stages.…”
Section: Dry Eye Overviewmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Prevalence of dry eye varies from 2% to 50%, depending on the population studied and the diagnostic criteria for dry eye (symptom questionnaire vs. objective signs). [1][2][3]6,7,[9][10][11][14][15][16][17][18][19][20][21][22][23] There is scarce information about the natural history of dry eye, but there is a recognized disconnection between signs and symptoms; patients tend to be more symptomatic at early stages. 24,25 Dry eye causes corneal irregularity [26][27][28] and decreases functional vision by altering contrast sensitivity [29][30][31] and, therefore, decreases quality of life with a significant burden on the individual as well as the society.…”
mentioning
confidence: 99%
“…The other main factor to develop dry eye is gender, it being more common in women than men. The Beaver Dam study showed a prevalence of dry eye of 18% in women and only 11% in men, and some other studies described even higher differences between women and men (Paulsen et al, 2014). The principal reason for these differences would be the hormonal factor (Guillon and Maissa, 2010).…”
Section: Presence In the Tear Film Of Healthy Patientsmentioning
confidence: 97%
“…Based on OSDI score, the ocular surface is defined as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), or severe (33-100) [44]. It is noteworthy that although the OSDI is not routinely used in clinical practice, it has been shown to be valid and reliable to quantify the impact of dry eye on the quality of life [44].…”
Section: Discussionmentioning
confidence: 99%